Analisis Manajemen Layanan E-Learning Thatquiz Pada SMK Negeri 5 Palembang Menggunakan Framework ITIL - Sri Tari Utami; Tata Sutabri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The rapid development of technology in the world of education requires schools to apply technology in the form of systems that support learning such as e-learning. SMK Negeri 5 Palembang is one of the schools that has used an E-learning called Thatquiz but has never measured the maturity level of the services provided to users, so it is not yet known whether the management of this E-learning service is in accordance with the vision and mission to be achieved by the school. The author measures the maturity level using the ITIL Version 3 framework with the Service Operation domain. By distributing questionnaires to 100 respondents consisting of students and teachers, the results of the analysis show that the maturity level of E-learning SMK Negeri 5 Palembang is at level 3, namely defined. While the expected maturity level is level 4, namely managed, GAP analysis is 1.20. recommendations given to the school to be able to achieve the level of expectation. Keywords: E-Learning, SMK Negeri 5 Palembang, Maturity Level, ITIL V3, Domain, Service operations